A short-term controlled trial of an adjustable oral appliance for the treatment of mild to moderate obstructive sleep apnoea. Issue 4 (April 1997) - Ferguson, K A; Ono, T; Lowe, A A; al-Majed, S; Love, L L; Fleetham, J A
Abstract : BACKGROUND: Although oral appliances are effective in some patients with obstructive sleep apnoea (OSA), they are not universally effective. A novel anterior mandibular positioner (AMP) has been developed with an adjustable hinge that allows progressive advancement of the mandible. The objective of this prospective crossover study was to compare efficacy, side effects, patient compliance, and preference between AMP and nasal continuous positive airway pressure (nCPAP) in patients with symptomatic mild to moderate OSA. METHODS: Twenty four patients of mean (SD) age 44.0 (10.6) years were recruited with a mean (SD) body mass index of 32.0 (8.2) kg/m2, Epworth sleepiness score 10.7 (3.4), and apnoea/hypopnoea index 26.8 (11.9)/hour. There was a two week wash-in and a two week wash-out period and two treatment periods (AMP and nCPAP) each of four months. Efficacy, side effects, compliance, and preference were evaluated by a questionnaire and home sleep monitoring. RESULTS: One patient dropped out early in the study and three refused to cross over so treatment results are presented on the remaining 20 patients. The apnoea/hypopnoea index (AHI) was lower with nasal CPAP 4.2 (2.2)/hour than with the AMP 13.6 (14.5)/hour (p < 0.01). Eleven of the 20 patients (55%) who used the AMP were treatment successes (reduction of AHI to < 10/hour and relief of symptoms), one (5%) was a compliance failure (unable or unwilling to use the treatment), and eight (40%) were treatment failures (failure to reduce AHI to < 10/hour and/or failure to relieve symptoms). Fourteen of the 20 patients (70%) who used nCPAP were treatment successes, six (30%) were compliance failures, and there were no treatment failures. There was greater patient satisfaction with the AMP (p < 0.01) than with nCPAP but no difference in reported side effects or compliance. CONCLUSIONS: AMP is an effective treatment in some patients with mild to moderate OSA and is associated with greater patient satisfaction than nCPAP.